1989
DOI: 10.1152/jappl.1989.67.1.270
|View full text |Cite
|
Sign up to set email alerts
|

Activation of masseter muscles with inspiratory resistance loading

Abstract: Closure of the jaw exerts traction on muscles that insert on the hyoid bone and that may stabilize or expand the pharyngeal airway. We postulated that the masseter muscles, which close the jaw, would be activated when the patency of the pharyngeal airway is threatened. We therefore measured electromyographic activation of the masseters during inspiratory resistance loading and compared it with activation of chin muscles and alae nasi in 10 normal subjects. We observed no masseter activation during quiet unload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Remmers et al (1978) reported that the genioglossal electromyogram in patients with obstructive sleep apnea syndrome consistently revealed periodicity; low level activity at the onset of obstruction and prominent discharge at the instant of pharyngeal opening. Hollowell & Suratt (1989) found that masseter muscle activation occurred in patients with obstructive sleep apnea syndrome and in a pattern similar to that of submental muscles. Also in the present study the masseter muscle, the genioglossal muscle and the inferior head of the lateral pterygoid muscle showed lower amplitudes during obstructive apnea and higher amplitudes after the apnea (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Remmers et al (1978) reported that the genioglossal electromyogram in patients with obstructive sleep apnea syndrome consistently revealed periodicity; low level activity at the onset of obstruction and prominent discharge at the instant of pharyngeal opening. Hollowell & Suratt (1989) found that masseter muscle activation occurred in patients with obstructive sleep apnea syndrome and in a pattern similar to that of submental muscles. Also in the present study the masseter muscle, the genioglossal muscle and the inferior head of the lateral pterygoid muscle showed lower amplitudes during obstructive apnea and higher amplitudes after the apnea (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…1). The coactivation of agonist (the genioglossal muscle and the lateral pterygoid muscle) and antagonist (the masseter muscle) after the apnea was postulated to stabilize the mandible to prevent the upper airways from collapsing (Hollowell & Suratt, 1989). Hollowell & Suratt (1991) reported that the jaws of patients with obstructive sleep apnea were open more widely than those of normal subjects at the end of expiration and opened further at the end of inspiration, particularly at the termination of apneas when the masseter and submental muscles contracted.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, trigeminal motoneurons display rhythmic respiratory activity in newborn rodents (e.g. Jacquin et al, 1999;Koizumi et al, 1999Koizumi et al, , 2002 and even in humans especially under particular conditions (Sauerland et al, 1981;StJohn and Bledsoe, 1985;Hollowell and Suratt, 1989;Hollowell et al, 1991). These findings may possibly account for the persistence of vestiges of the original trigeminal oscillator and for the high homology between the pTRG and the preBötC.…”
Section: Considerations On the Evolutionary Trends In Respiratory Rhymentioning
confidence: 99%
“…However, REM sleep stage has a fixed effect of MM amplitude reduction reflecting the reduction in neural respiratory drive to the respiratory musculature associated with this sleep stage. Beyond central respiratory drive originating in the brainstem impacting motoneurons innervating the diaphragm, there are active nuclei involved in the recruitment and relaxation of muscles controlling MM (33). These nuclei are also independently subjected to REM sleep atonia (34).…”
Section: Discussionmentioning
confidence: 99%